Role of leucine-rich pentatricopeptide repeat motif-containing protein (LRPPRC) for anti-apoptosis and tumourigenesis in cancers - Tian, Tian; Ikeda, Jun-Ichiro; Wang, Yi; Mamat, Suhana; Luo, Wenjuan; Aozasa, Katsuyuki; Morii, Eiichi (Elsevier Inc., 2012)
Due to accelerated energy consumption, enhanced function of mitochondria in tumour cells compared to normal cells is prerequisite for tumour development. Leucine-rich pentatricopeptide repeat motif-containing protein (LRPPRC) regulates the expression of all mitochondrial DNA-encoded mRNAs, thus plays an important role in the mitochondrial function. LRPPRC is abundantly expressed in the side population of lung adenocarcinoma cell lines, where cancer stem cells are enriched. However, the role of LRPPRC in tumour development remained to be clarified in detail. Here, the expression of LRPPRC was examined in various types of tumours, such as lung adenocarcinoma, oesophageal squamous cell carcinoma, stomach, colon, mammary and endometrial adenocarcinoma, and lymphoma. Immunohistochemistry revealed that all kinds of examined tumours abundantly expressed LRPPRC. In contrast, surrounding non-neoplastic cells hardly expressed LRPPRC. The knocked-down expression of LRPPRC in lung adenocarcinoma cells did not affect amount of side population and activity of aldehyde dehydrogenase 1, known to be highly expressed in cancer stem cells of the lung. However, the knocked-down expression of LRPPRC reduced the abilities for anti-apoptosis, invasion and in vitro colony formation in lung adenocarcinoma, as well as Hodgkin lymphoma cells. Double staining of LRPPRC with active caspase-3 in clinical samples of lung adenocarcinoma revealed that apoptotic cells were hardly observed in LRPPRC-expressing tumours. These findings indicate that LRPPRC played an important role in tumourigenesis through the resistance to apoptosis and high invasive activity.